EXAMINING NUTRITIONAL STATUS AND EMOTIONAL WELL BEING IN ADOLESCENT GIRLS THROUGH DIET QUALITY AND DEPRESSIVE SYMPTOMS: NUTRITIONAL STATUS AND EMOTIONAL FUNCTIONING IN ADOLESCENT GIRLS - S.SAI JANANI; K. LAKSHMI; G. NIRMALA DEVI; BILQUIS (The Journal of Research ANGRAU, 2026)
Adolescence is a critical developmental stage marked by heightened nutritional demands and emotional sensitivity, particularly among girls. The present study was conducted in the year 2024 with an objective to assess the diet quality and emotional functioning of 100 adolescent girls aged 11–18 years in Guntur district of Andhra Pradesh- using the Diet Quality Index– International (DQI-I) and the Depression, Anxiety, and Stress Scale–Youth Version (DASS-Y). Dietary Information was gathered via 24-hour recall and evaluated using Indian Food Composition Table IFCT (2017), with DQI-I scoring based on ICMR–NIN (2020) guidelines. Emotional functioning was evaluated using DASS-Y, categorizing severity across depression, anxiety and stress. Data on DQI-I scoring showed that 15 percent of the girls had excellent diet quality, 85 percent were under the “Good but Needs Improvement” category (>60–80) and none had poor diet quality (<60). Results of DASS-Y showed high emotional distress 86percent had moderate to extremely severe anxiety, 79 percent had moderate to severe stress, and 72 percent showed depressive symptoms. Older adolescents (15–18 years) exhibited significantly higher levels of stress and anxiety compared to younger ones, as confirmed by t-tests and chi-square analyses. A strong negative correlation (r = -0.6798, p < 0.001) was observed between DQI-I and DASS-Y scores, with 46.21 percent of the emotional variation explained by diet quality. These findings underscore the critical role of nutrition in mental health and highlight the need for integrated dietary and psychological interventions to promote holistic well-being among adolescent girls.